KETIDAKADILAN GENDER TERHADAP PEREMPUAN DALAM NOVEL TEMPURUNG KARYA OKA RUSMINI: PENDEKATAN FEMINISME SASTRA - Zun Afifah Nurrahmah; Sri Wahyuningtyas (CARAKA, 2019)
This research aims as follows. (1) Describe the elements of the novel which include the plot, character and characterization, and background in the novel Tempurung by Oka Rusmini. (2) Describe gender injustice found in the novel Tempurung by Oka Rusmini. (3) Describe the response of figures who experienced gender injustice in the novel Tempurung by Oka Rusmini. This type of research is qualitative research. The results obtained in this study are as follows. (1) The flow in the Tempurung novel uses the regression path. The main character in Novel Tempurung is Dayu and the additional character is Mrs. Barla. Both have diverse characters. Background of most places on the island of Bali. The time frame described after the terrorist attacks of 11 September 2001 and after the Bali Bombing I incident on 12 October 2002. While the social background illustrates the condition of the Balinese people with their customs. (2) Gender injustice towards women in Tempurung novels is marginalization, subordination, stereotyping, violence and workload. (3) The response of leaders who experience gender inequality, namely, choosing to remain silent, resist, and continue to struggle until finally becoming independent women.